“POWER DAN SALIDARITAS ELITA INDONESIA PADA ERA REFORMASI REFLEKSI PADA PRONOMINA PERSONA PEMAKAIAN BAHASA INDONESIA” - I Nyoman Darsana (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Abstract The reformation commencing since 1998, has not just had the effect toward sociopolitical, socio-economy and Indonesian cultural changes, but also it has the effect toward the usage of Indonesian language. One of the effects is the appearance of Power and Solidarities in using pronominal personals, both the first, second or the third pronominal personals. This writing tries to review the usage and the rule of power and solidarity of the first, second and third pronominal personals. Well, pronominal personals aku, ku, engkau, and kalian are really no longer used anymore in this Reformation era. Even it is common taken place that the first singular personal are often used as kami. The second pronominal personal engkau and kamu are seldom used. On the other hand, the form of anda and kalian or saudara are more frequently used. The pronominal beliau for the third person referring to the rule is common for the word superior, and in this reformation era is used for kamu as superior